2012
DOI: 10.1503/cmaj.110900
|View full text |Cite
|
Sign up to set email alerts
|

The lost sponge: patient safety in the operating room

Abstract: A 43-year-old woman presented to the emergency department with acute nausea and vomiting. She was admitted by the general surgery team with a suspected obstruction of the small bowel. Examination and imaging revealed an enlarged uterus (18 × 9 × 16 cm) with fibroids. Nine years earlier, she had undergone a uterine myomectomy by means of midline laparotomy, after which postoperative pancreatitis and bleeding had occurred followed by repeat laparotomy.The next morning (midweek), a laparotomy was performed to ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…This also highlights the need for consistent guidelines and count policies. Henceforth, institutions should amend their policy on sponge and count 16…”
Section: Discussionmentioning
confidence: 99%
“…This also highlights the need for consistent guidelines and count policies. Henceforth, institutions should amend their policy on sponge and count 16…”
Section: Discussionmentioning
confidence: 99%
“…Several factors have been associated with gossypibomas, such as operations performed as emergencies; inaccurate recording of swab counts; unexpected intraoperative events, findings, or adjustments; and patient factors, such high body mass index (BMI) and female sex. 5 The clinical picture may include abdominal pain, abdominal mass, rectal bleeding, intestinal obstruction, fever, diarrhoea and weight loss 6 ; the time of presentation and duration can vary from 3 days to 40 years, 7 which makes early diagnosis difficult.…”
Section: Discussionmentioning
confidence: 99%
“…•The nature of the intra-operative procedure [8,9] •Noncompliance with protocols [10][11][12] •lack of conducting a surgical count [8] •Incorrect surgical counts [4,13,14] •Higher body mass index [3] •More than one sub-procedure [4,8] •More than one surgical team [8] •Longer duration of surgery [13] •Emergencies with unplanned changes in [2,3,13] •Equipment failure [15] •Elements of teamwork including leadership, human factors, and communication [12,14,16] •Distraction, multitasking, and time pressure [9][10][11] •An increased number of perioperative personnel and specialty teams involved [2] Search methodology…”
Section: Eligibility Criteriamentioning
confidence: 99%
“…The ratings on the different items were used by the reviewers to assess the risk of bias in the study due to flaws in study design or implementation. A score was given to classify the quality of each paper as poor (0-6), fair (7)(8)(9)(10)(11), or good (12)(13)(14)(15)(16). In general terms, a ''poor'' rating indicated significant risk of bias, a ''fair'' study indicated some bias deemed not sufficient to invalidate its results, and a ''good'' study had the least risk of bias, so that the results were considered to be valid.…”
Section: Quality Of Included Studies and Risk For Biasmentioning
confidence: 99%